PILIHAN PEMBIAYAAN KESEHATAN MASYARAKAT DI KECAMATAN DENPASAR SELATAN KOTA DENPASAR PROVINSI BALI - Widi Pratama, I Kadek Angga; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 11 (2022): vol.11.11. NOVEMBER 2022[4011-4233], 2022)
The problem that often occurs in the case of additional insurance markets is the existence of imperfect information which results in the market being unable to allocate resources efficiently. Because the public has the power to decide whether or not to buy an additional insurance product, policies for the provision of public health services through the redistribution of wealth through the insurance industry are susceptible to adverse selection problems. The research objective to be achieved is to find out whether adverse selection occurs in the additional insurance market in South Denpasar District. This research was conducted in South Denpasar District with a total sample of 100 people. Variables used in this study, namely additional insurance, chronic conditions, self-care activities, log family income, and partner status through interviews and distribution of questionnaires. The collected data were then analyzed using binary logistic analysis techniques, goodness of fit tests, and partial tests (t-test). The results of the study show that chronic conditions have a partial positive effect on Additional Insurance in South Denpasar District. Self Care Activity does not have a partial positive effect on Additional Insurance in South Denpasar District. Family Income Log has a partial positive effect on Additional Insurance in South Denpasar District. Spouse status has no partial positive effect on Additional Insurance in South Denpasar District.